Bifunctional CO oxidation over Mn-mullite anchored Pt sub-nanoclusters via atomic layer deposition. Issue 9 (6th February 2018) - Liu, Xiao; Tang, Yuanting; Shen, Meiqing; Li, Wei; Chu, Shengqi; Shan, Bin; Chen, Rong
Abstract : Highly dispersed Pt sub-nanoclusters are anchored on SmMn2 O5 mullites via atomic layer deposition, and show excellent low-temperature CO oxidation activity. Abstract : CO oxidation is a widely used model system for understanding fundamental aspects of heterogeneous catalysis. While platinum (Pt) continues to be a reference material for CO oxidation catalysis, poisoning of Pt catalysts presents a critical issue that blocks reaction sites and impedes subsequent reaction steps. Fabrication of CO poison-free Pt catalysts remains a great challenge due to its CO-philic nature. Herein, we report a Pt based catalyst to effectively tackle CO poisoning by tightly anchoring Pt sub-nanoclusters onto Mn-mullite oxide (SmMn2 O5 ) via atomic layer deposition. Superior CO oxidation activity has been observed with a significantly lowered light-off temperature and apparent activation energy. In situ diffuse reflectance infrared Fourier transform spectroscopy analysis, oxygen isotope experiments and density functional theory calculations confirm that the low-temperature activity originates from active oxygen atom sources at the bifunctional interface structure.